Hafnium carbide as a novel nanofiller for RT64HC phase change materials: Enhancing thermal conductivity, heat capacity, and cycling stability - Gurgenc, Ezgi; Öztop, Hakan Fehmi; Senocak, Safak Melih; Aktemur, Cenker; Gurgenc, Turan; Varol, Yasin; Gur, Muhammed (Elsevier, 2026)
Improving the thermophysical performance of organic phase change materials (PCMs) is essential for efficient low-to medium-temperature latent heat thermal energy storage (LHTES) systems. In this work, RT64HC paraffin was reinforced with HfC nanoparticles (0.5-2.0 wt%) using a controlled multi-step dispersion method that combined surfactant-assisted stirring with ultrasonication. Structural and spectroscopic analyses (XRD, FT-IR, FE-SEM/EDX) confirmed uniform nanoparticle distribution without chemical reaction or phase segregation. Thermophysical measurements showed significant improvements. In the solid phase, thermal conductivity increased from 0.21 to 0.367 W/m.K (74.76 %) while in the liquid phase it rose from 0.177 to 0.235 W/m.K (32.76 %). Specific heat capacity increased from 1.42 to 1.87 J/g.K (31.69 %) in the solid phase and from 2.29 to 2.91 J/g.K (27.07 %) in the liquid phase within the 73-80 degrees C window. Differential scanning calorimetry (DSC) revealed excellent cycling durability with enthalpy retention of 97.2-99.2 % after 1000 cycles and effective suppression of supercooling (Delta T <= 0.06 degrees C). Thermogravimetric analysis (TGA) demonstrated enhanced thermal stability with onset degradation temperature reaching about 192 degrees C at 1.0-1.5 wt% and 185.2 degrees C at 2.0 wt% while maximum decomposition temperature increased to 343.62 degrees C. Residual mass rose from 7.81 % to 12.61 %, indicating improved high-temperature resistance. Compared with conventional fillers, HfC enables superior conductivity and stability at low loading while reducing agglomeration and enthalpy fading. These advantages highlight HfC/RT64HC nanocomposites as promising candidates for renewable and sustainable energy applications including solar collectors, building envelopes, electronic cooling, battery regulation, waste heat recovery and thermal batteries.
Keywords: Phase change material; RT64HC; Hafnium carbide; Nanocomposite; Thermal conductivity; Thermal energy storage